Aktivitas Antioksidan Ekstrak Tubuh Buah Jamur Paha Ayam (Coprinus comatus) dengan Pelarut Berbeda - Agus Susanto; Nuniek Ina Nuniek; Nuraeni Ekowati (Fakultas Biologi | Universitas Jenderal Soedirman, 2018)
Coprinus comatus or with local name is drum stick chiken mushroom that includes edible and medicinal mushroom. This mushroom contains bioactive compounds that have several pharmacological effects, like as antibacterial, anticancer, immunomodulator, anti-inflammatory, prevent diabetes and antioxidant. bioactive compounds includes in fruit body C. comatus can be obtained by extraction used solvent. The objective of this study was to determine whether the C. comatus fungus was potential as an antioxidant producer and to know which solvent produced the best antioxidant activity from the extract of the fruit body of C. comatus. The method used in this research is experimental with two treatments ie n-hexane and ethanol 70% solvent. Fruit body of C. comatus is extracted by maceration method, then the viscous extract obtained by phytochemical test and antioxidant activity test using DPPH method (1,1-diphenyl-2-picrihidazil). The results obtained are then analyzed using t-test for independent samples. The results showed that the average yield of ethanol extract 70% higher than n-heksan were each 61.33% ± 9,21 and 14.8% ± 0,87. The test of total phenol extract ethanol was 70% higher than n-hexane , each with an average of 325,19 ppm ± 50,01 and 110,08 ppm ± 34,67. The result of antioxidant activity test using DPPH method of ethanol extract 70% and n-heksan has IC50 value 2,48 mg/ml and 3,86 mg/ml. Phytochemical test results for flavonoid test showed positive result for both samples extract, terpenoid test showed positive result in both samples , the tannin test showed negative results in both samples.